2020
DOI: 10.1093/neuonc/noaa215.938
|View full text |Cite
|
Sign up to set email alerts
|

Tami-51. Identifying New Tumor Microenvironment (Tme) Contexts of Vulnerability in Glioblastoma

Abstract: Glioblastoma (GBM) is the most frequent and aggressive adult brain tumor with 85% of patients dying within two years. New effective precision medicine therapies are urgently required, especially for isocitrate dehydrogenase wild-type (IDHwt) disease. Despite efforts to subtype patients based on molecular profiles, this approach has yet failed to direct treatment strategies. Further interrogation of the tumor microenvironment (TME) across molecular subtypes and identification of new TME specific subtypes may gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…In 2019, using a 500-gene set classifier (only 108 genes matched Verhaak et al's 840-gene set) on six different datasets (three TCGA-cohorts and three Asian-cohorts), Teo et al also confirmed the classical, mesenchymal, and proneural subtypes, with similar survival outcomes between subtypes (293). Finally, in 2023, White et al also found no significant difference in overall survival between subtypes in the GLIOTRAIN (n=123), TCGA (n=164), and CGGA (n=693) cohorts after stratifying the mesenchymal, proneural, and classical subtypes according to Wang et al' report (294). Interestingly, the authors introduced novel glioblastoma tumor microenvironment subtypes for IDH wild type glioblastoma (TME High , TME Med , and TME Low ), characterized by significantly different expression of genes specific to all immune and endothelial cell markers.…”
Section: The Immune Landscape and Prognostic Significance Of Mesenchy...mentioning
confidence: 81%
See 2 more Smart Citations
“…In 2019, using a 500-gene set classifier (only 108 genes matched Verhaak et al's 840-gene set) on six different datasets (three TCGA-cohorts and three Asian-cohorts), Teo et al also confirmed the classical, mesenchymal, and proneural subtypes, with similar survival outcomes between subtypes (293). Finally, in 2023, White et al also found no significant difference in overall survival between subtypes in the GLIOTRAIN (n=123), TCGA (n=164), and CGGA (n=693) cohorts after stratifying the mesenchymal, proneural, and classical subtypes according to Wang et al' report (294). Interestingly, the authors introduced novel glioblastoma tumor microenvironment subtypes for IDH wild type glioblastoma (TME High , TME Med , and TME Low ), characterized by significantly different expression of genes specific to all immune and endothelial cell markers.…”
Section: The Immune Landscape and Prognostic Significance Of Mesenchy...mentioning
confidence: 81%
“…Interestingly, the authors introduced novel glioblastoma tumor microenvironment subtypes for IDH wild type glioblastoma (TME High , TME Med , and TME Low ), characterized by significantly different expression of genes specific to all immune and endothelial cell markers. However, stratification into these new subtypes showed no association with overall survival in the GLIOTRAIN, TCGA, CGGA, and DUKE cohorts (294).…”
Section: The Immune Landscape and Prognostic Significance Of Mesenchy...mentioning
confidence: 85%
See 1 more Smart Citation
“…Another source of complexity influencing heterogeneity is given by the tumor microenvironment (TME) [23]. TME is not constituted only by cancerous cells, but also by different populations of immune cells, stromal cells, endothelial cells, and pericytes, creating different types of niches within the tumor [24].…”
Section: Heterogeneity Of Gbmmentioning
confidence: 99%
“…One of the hypothesized reasons for the aggressiveness and treatment resistance displayed by GBM is its complex spatial organization, seemingly seeking to mimic the spatial architecture of its s u r r o u n d i n g m i c r o e n v i r o n m e n t . T h e G B M t u m o r microenvironment (TME) is comprised of endothelial cells, neurons, astrocytes, oligodendrocytes, microglia, tumor-associated macrophages, tumor-infiltrating lymphocytes, and noncellular components such as apocrine and paracrine signaling molecules, exosomes, extracellular matrix (ECM) components, and secreted ECM remodeling enzymes (32,33). Each of these components play not only individual roles but also orchestrate an incredibly complex and spatially distinct TME in which GBM can evade immune system detection and uncontrollably proliferate.…”
Section: Introductionmentioning
confidence: 99%